A weak neutralizing antibody response to hepatitis C virus envelope glycoprotein enhances virus infection. - Keith Meyer; Arup Banerjee; Sharon E Frey; Robert B Belshe; Ranjit Ray (PLoS ONE)
We have completed a phase 1 safety and immunogenicity trial with hepatitis C virus (HCV) envelope glycoproteins, E1 and E2, with MF59 adjuvant as a candidate vaccine. Neutralizing activity to HCV genotype 1a was detected in approximately 25% of the vaccinee sera. In this study, we evaluated vaccinee sera from poor responders as a potential source of antibody dependent enhancement (ADE) of HCV infection. Sera with poor neutralizing activity enhanced cell culture grown HCV genotype 1a or 2a, and surrogate VSV/HCV pseudotype infection titer, in a dilution dependent manner. Surrogate pseudotypes generated from individual HCV glycoproteins suggested that antibody to the E2 glycoprotein; but not the E1 glycoprotein, was the principle target for enhancing infection. Antibody specific to FcRII expressed on the hepatic cell surface or to the Fc portion of Ig blocked enhancement of HCV infection by vaccinee sera. Together, the results from in vitro studies suggested that enhancement of viral infectivity may occur in the absence of a strong antibody response to HCV envelope glycoproteins.